A synopsis of carbonation of alkali-activated materials. Issue 3 (21st January 2019) - Rashad, Alaa M
Abstract : Carbonation in concrete is the formation of calcium carbonate (CaCO3 ) in the binder by a chemical reaction. It results when ions of carbonate from dissolved carbon dioxide (CO2 ) react with calcium ions (Ca + ) in the binder and precipitate calcium carbonate. The major effect of carbonation is the destruction of the passive layer forming on steel bars, leading to corrosion. In addition, carbonation can affect the mechanical strength, absorbed water and porosity of the matrix. In the literature, there are limited studies relevant to carbonated alkali-activated materials (AAMs) in comparison with those on plain Portland cement or blended cement with different materials. The present paper summarizes the available studies relevant to the effect of carbonation on both solely and blended AAMs. The carbonation depth, mechanical strength, absorbed water, porosity and corrosion risk of carbonated AAMs are discussed. The current review showed that, in most cases, AAMs have higher susceptibility to carbonation than PC. Dosage and modulus ratio of the activator have an essential effect on carbonation depth of alkali-activated slag (AAS). Mechanical strength decreased, whilst porosity increased in a carbonated AAS matrix. Carbonation of alkali-activated metakaolin did not show a harmful effect over time on the compressive strength or risk of corrosion, but showed a significant risk of efflorescence.